2020
DOI: 10.1017/s1368980020001585
|View full text |Cite
|
Sign up to set email alerts
|

Food group intake at self-reported eating occasions across the day: secondary analysis of the Australian National Nutrition Survey 2011–2012

Abstract: Objective: To examine core and discretionary food and beverage intake at eating occasions, and to explore the variation in consumption by age and gender in Australian adults and children. Design: The study utilised one 24-h dietary recall with self-reported eating occasions from a nationally representative sample of Australians. Average servings of each food group for age and gender subpopulations were compared with the Australian Dietary Guidelines. The percentage contribution of each e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…A study investigating intake of South Australian primary schoolaged children (8-11 years) in 2010 showed that children were consuming fruit or discretionary choices during morning snack break, and sandwiches during the lunch break (12) . Further evidence has shown that over half of children's total day intake of discretionary choices occurs during snack eating occasions (37) , which corresponds with common morning snack breaks in Australian schools. To address commonly consumed discretionary choices, school-based interventions may consider targeting snack eating occasions in school, to encourage vegetable snack consumption (21) , and discourage high sugar, fat and/or Na food and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating intake of South Australian primary schoolaged children (8-11 years) in 2010 showed that children were consuming fruit or discretionary choices during morning snack break, and sandwiches during the lunch break (12) . Further evidence has shown that over half of children's total day intake of discretionary choices occurs during snack eating occasions (37) , which corresponds with common morning snack breaks in Australian schools. To address commonly consumed discretionary choices, school-based interventions may consider targeting snack eating occasions in school, to encourage vegetable snack consumption (21) , and discourage high sugar, fat and/or Na food and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…However, this would require significant dietary change for most Australians (intake of legumes would need to increase by about 20-fold). Substantially increasing legume consumption would be a big cultural shift for Australians, as they are not commonly part of meals [ 44 ]. Reductions in animal meats can make it more difficult to achieve adequate iron and zinc intakes so careful meal planning is required, particularly as the bioavailability of these nutrients is lower in plant-based foods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a need to encourage the number of eating occasions when vegetables are included. In Australia, vegetables are predominantly consumed with dinner [ 78 , 79 ]. Vegetable intake could be increased if the types of meals containing vegetables were also consumed more frequently for lunch and at other times during the day.…”
Section: Discussionmentioning
confidence: 99%